DSS Decision Support System for Best Employee Evaluation Using the SMART Algorithm. - Handayani, Dwipa; Rasim, Rasim (International Journal of Information Technology and Computer Science Applications, 2024)
The use of information technology has permeated all areas, including employee performance evaluation, which plays a crucial role in company management. The success of a company is largely dependent on human resources, which are considered valuable assets due to their strong link to employee performance. This study focuses on the application of the SMART Algorithm in a Decision Support System designed for the evaluation of the best employees at PT Raharja Jaya Mandiri Bekasi. The main objectives of the study are to develop an employee evaluation system, apply the SMART Algorithm to make the evaluation process more objective, and improve the security and reliability of evaluation data through a digital system. The research employs the SMART Algorithm to evaluate and select the best option based on predetermined goals and criteria. This approach is implemented using the waterfall model of system development. The results of the study indicate that the implementation of a web-based Decision Support System utilizing the SMART Algorithm enhances the accuracy and efficiency of employee performance evaluations at PT Raharja Jaya Mandiri Bekasi. Moreover, it reduces subjective bias in the decision-making process and ensures that the best employees are chosen based on measurable and transparent criteria.